Phase II multicentre trial of oral quisinostat, a histone deacetylase inhibitor, in patients with previously treated stage IB–IVA mycosis fungoides/Sézary syndrome3. (2nd June 2016) - Child, F.; Ortiz‐Romero, P.L.; Alvarez, R.; Bagot, M.; Stadler, R.; Weichenthal, M.; Alves, R.; Quaglino, P.; Beylot‐Barry, M.; Cowan, R.; Geskin, L.J.; Pérez‐Ferriols, A.; et al.
Abstract : What's already known about this topic? Histone deacetylase inhibitors (HDAC‐Is) have been associated with significant clinical activity in different neoplastic disorders. Vorinostat and romidepsin have been approved by the U.S. Food and Drug Administration for treatment of cutaneous T‐cell lymphoma (CTCL). Quisinostat is a hydroxamate, second‐generation, orally available pan‐HDAC‐I. What does this study add? Oral quisinostat 12 mg three times weekly is active in the treatment of patients with relapsed or refractory CTCL, and has an acceptable safety profile. There was a low global response rate of 8% vs. a cutaneous response rate of 24%. Combination therapy of quisinostat with other novel agents may be appropriate in patients who relapse following current conventional approaches. Linked Comment: Scarisbrick. Br J Dermatol 2016;175 :14–15 Plain language summary available online Summary: Background: Quisinostat is a hydroxamate, second‐generation, orally available pan‐histone deacetylase inhibitor. Objectives: To evaluate the efficacy and safety of oral quisinostat in patients with previously treated cutaneous T‐cell lymphoma (CTCL). Methods: Patients received quisinostat 8 mg or 12 mg on days 1, 3 and 5 of each week in 21‐day treatment cycles. Primary efficacy end point was cutaneous response rate (RR) based on the modified Severity Weighted Assessment Tool (mSWAT). Secondary end points included global RR, duration of response (DOR) in skin, progression‐free survival (PFS), pruritus relief, safety and pharmacodynamic markers. Results: Eight of 26 (25 evaluable) patients achieved ≥ 50% reduction in mSWAT score at least once, with confirmed cutaneous response in six (RR 24%). There was a low global RR of 8%. DOR in skin ranged from 2·8 to 6·9 months. Median PFS was 5·1 months. Pruritus relief was more frequent in cutaneous responders (67%) than nonresponders (32%). Serial tumour biopsies revealed an increase in acetylated tubulin, indicating a target effect of histone deacetylase 6. Twenty‐one of 26 (81%) patients were withdrawn from the study before or at clinical cut‐off; five (19%) continued to receive treatment with quisinostat. The most common drug‐related adverse events were nausea, diarrhoea, asthenia, hypertension, thrombocytopenia and vomiting. Grade 3 drug‐related adverse events included hypertension, lethargy, pruritus, chills, hyperkalaemia and pyrexia. Conclusions: Quisinostat 12 mg three times weekly is active in the treatment of patients with relapsed or refractory CTCL, with an acceptable safety profile. Combination therapy with other drugs active in CTCL may be appropriate.